Prevalence and Property of Colonic polyp and Adenoma among Iraqi Patients - Ali Hussein, Sajid; J Akayashy, Raghad (Diyala Journal of Medicine, 2023)
Background: Colorectal cancer (CRC) is the third common diagnosed. ‎cancer in the world, so that colonic polyp detection is important because colonic polyp is a precursor to CRC. Objective: To detect the prevalence of polyp and adenoma. Patients and Methods: A retrospective study was done using reports of endoscopic examination done previously for patients seen at gasteroenterology and hepatology hospital in Baghdad. Results: The study included 924 examination of colon, mean age of patients was 48.1 years. Polyps was detected in 128 colonoscopies. (PDR) was 16.7 %. The PDR was higher in patients ≥ 60 years old (25 %), while polyp detection rate was ( 17.7 % ) in those 50 – 59 years age group. Adenoma was found in 7.9 % of those with completed colonoscopies. It was higher in male patients (9.2 % ) than female patients (6.2%). It was highest in age group ≥ 60 years old (15.9%), while adenoma was found in (8.2 %) of those with age group of 50 – 59 years old. Conclusion: This study highlight on the prevalence of polyp (16.7%) and adenomas (7.9%) in patients underwent endoscopy for different indications, and give us an idea about screening for CRC in Iraq and at which age it should be started.